Historical Dictionary of Liberia - Dunn, Elwood D.; Beyan, Amos J.; Burrowes, Carl Patrick (Rowman & Littlefield Publishers, 2000)
Originally formed to harbor freed slaves and Americans returning to Africa, Liberia once was a land of hope. That was shattered by a long Civil War that shook its very foundation. Today's Liberia is glimpsed in this second edition. Building on the first edition, this updated volume focuses on the personalities, from the founders of Liberia, to the soldiers who are responsible simultaneously for destruction and the hope of stability. Along with these people, various social and ethnic groups, political parties and labor movements, economic entities and natural resources are profiled in this updated work. A new chronology of Liberia is included, and a selected bibliography suggests further readings for the scholar.